1999
DOI: 10.1136/jamia.1999.00660313
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Computerized Physician Order Entry on Medication Error Prevention

Abstract: Computerized POE substantially decreased the rate of non-missed-dose medication errors. A major reduction in errors was achieved with the initial version of the system, and further reductions were found with addition of decision support features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
618
2
30

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,025 publications
(666 citation statements)
references
References 20 publications
16
618
2
30
Order By: Relevance
“…9 In another report, CPOE with clinical decision-support software led to a more dramatic reduction of 81%. 10 Additionally, pharmacist involvement on medical rounds has reduced adverse drug events by 78%. 11 The frequency of prescribing errors found in this study was similar to that found in previous literature, although the variation in the definitions limits this comparison somewhat.…”
Section: Discussionmentioning
confidence: 99%
“…9 In another report, CPOE with clinical decision-support software led to a more dramatic reduction of 81%. 10 Additionally, pharmacist involvement on medical rounds has reduced adverse drug events by 78%. 11 The frequency of prescribing errors found in this study was similar to that found in previous literature, although the variation in the definitions limits this comparison somewhat.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Decision support describes a technique in which diagnostic and management recommendations are provided to clinicians, usually at the point-of-care, and has been shown to improve care, 12,13 decrease costs, 14,15 and reduce errors. 16,17 Kaushal et al 18 identified critically ill neonates receiving intravenous infusions as one of the highest-risk population with a three-fold greater risk for medication order errors. Electronic physician order entry systems reduce serious medical errors by 55 to 81%, 16,19 and prototypic neonatal nutrition systems have been described.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Kaushal et al 18 identified critically ill neonates receiving intravenous infusions as one of the highest-risk population with a three-fold greater risk for medication order errors. Electronic physician order entry systems reduce serious medical errors by 55 to 81%, 16,19 and prototypic neonatal nutrition systems have been described. 20,21 Despite the potential advantages of clinical decision support, it is used infrequently.…”
Section: Introductionmentioning
confidence: 99%
“…15 Electronic physician order entry with real-time practice guidance 16,17 represents the best long term solution for neonatal PN order design to reduce errors and risk of injury to VLBW infants. 18,19 VLBW infants receiving intravenous PN were identified by Kaushal et al 20 as one of the highest risk groups for medical error related injury because of their multiple complex intravenous infusions, narrow therapeutic range and low tolerance for pharmaceutical errors. Electronic order entry and design can significantly reduce medical errors 21,22 and improve PN mineral content.…”
Section: Discussionmentioning
confidence: 99%